Outcomes with alemtuzumab induction therapy in lung transplantation: a comprehensive large‐scale single‐center analysis. (16th November 2021) - Benazzo, Alberto; Auner, Sophia; Boehm, Panja M.; Morscher, Annika; Schwarz, Stefan; Vidmar, Bogdan; Dzubur, Fedja; Schweiger, Thomas; Hoda, Ali M.; Moser, Bernhard; Matilla, Jose R.; Muraközy, Gabriella; et al.
Summary: Alemtuzumab is a monoclonal antibody targeting CD52, increasingly used as induction therapy after transplantation. The aim of this study was to analyze the outcomes of alemtuzumab induction therapy followed by a low‐dose maintenance immunosuppression in a large single‐center cohort of lung transplant recipients. All patients, who received alemtuzumab induction followed by a low‐dose maintenance immunosuppression were included in the analysis. Short‐ and long‐term outcomes were analyzed. 721 lung transplant recipients, transplanted between January 2008 and June 2019, were included in this retrospective study. Freedom from higher‐grade ACR at 1, 5, and 10 years was 98%, 96%, and 96%, respectively. Thirty‐nine patients (5%) developed clinical AMR. Twenty‐one percent of patients developed high‐grade CKD. A total of 1488 infections were recorded. Sixteen percent were diagnosed within the first 3 months. Sixty‐two patients (9%) developed a malignancy during follow‐up. Freedom from CLAD at 1, 5, and 10 years was 94%, 72%, and 53%, respectively. Overall survival rates at 1, 5, and 10 years were 85%, 71%, and 61%, respectively. Alemtuzumab induction combined with a low‐dose tacrolimus protocol is safe and associated with low rates of acute and chronic rejection, as well as an excellent long‐term survival. Abstract : This single‐center study represents the first large‐scale analysis of long‐term outcomes of alemtuzumab induction therapy, followed by a low‐dose dual drug maintenance immunosuppression after lung transplantation. The results presented in the manuscript show excellent long‐term outcomes, with low rates of severe infections and malignancies.